Dried blood spot as an alternative sample for screening of fatty acid, amino acid, and keto acid metabolism in humans - Laštovičková, Lenka; Kopčil, Michal; Kanďár, Roman (John Wiley & Sons Ltd., 2022)
Dried blood spot (DBS) is a simple and noninvasive sample collection technique allowing self-collection at home. It can be used as an alternative sample for the screening of metabolism in humans because changes in the levels of some fatty acids (FAs), amino acids (AAs), and keto acids (KAs) can be associated with metabolic disorders (e.g., diabetes mellitus). In this study, we optimized three different methods that are sensitive enough for the determination of the aforementioned analytes from a small volume of biological material in DBS. A total of 20 AAs, 5 KAs, and 24 FAs were determined. This sampling technique was applied to prepare samples from 60 individuals by a finger prick. The samples were analyzed using chromatographic methods, and acquired data were statistically evaluated. Even though most analytes were higher in men, only five AAs, three KAs, and eight FAs showed significant gender dependency (alpha = 0.05). Asparagine, serine, and alpha- and gamma-linolenic acids showed significant age dependency (alpha = 0.05). Most statistically significant correlations were positive and were found within one category. This work shows that because of many benefits, the DBS sample could be a good alternative to whole blood sample collection for the screening of metabolism in humans, in general, or in individualized medicine. The chromatographic methods can be used in future research, for example, to set the reference range or plasma-correction factors (various aspects such as age or gender should be considered).
Suchá kapka krve jako alternativní vzorek pro screening metabolismu mastných kyselin, aminokyselin a oxokyselin u lidí
Keywords: amino acids; chromatography; dried blood spot; fatty acids; keto acids; aminokyseliny; chromatografie; suchá kapka krve; mastné kyseliny; oxokyseliny